Palimpsest in the Novel The End or Wind of North by Hamida Shenoufi - Sahnine, Ali (LANGUAGE ART, 2024)
This paper examines a striking phenomenon in Algerian literature: the palimpsest, exemplified in Hamida Shenoufi’s novel The End or Wind of North. The study aims to uncover the elements of palimpsestic interplay between the secondary text (Wind of North ) and the source text (South Wind by Abdelhamid Ben Haddouga) at the levels of title, characters, literary language, narrative events, time, and space. It also explores the forms of interaction, resonance, and dialogue between the two texts in terms of aesthetics and content, while probing the hidden layers of the text to reveal its implicit meanings and the motivations behind the palimpsestic process. To achieve these objectives, the structuralist approach was employed to analyze the formal structure of the texts, and hermeneutics was used to interpret the semantic dimensions of intertextuality and palimpsest. The findings suggest that the author’s goal was not merely to achieve intertextuality with South Wind but also to articulate the unspoken in the original novel and propose an ending to its open conclusion. Thus, Wind of North answers questions left unresolved in South Wind, such as the failure of agricultural reform laws and the ideological conflicts that led to Algeria’s bloody decade. This study is pioneering in Algerian literary criticism, as it is the first to analyze the novel from a palimpsestic perspective.